Current and future antenatal management of isolated congenital diaphragmatic hernia. Issue 6 (December 2017) - Russo, Francesca Maria; De Coppi, Paolo; Allegaert, Karel; Toelen, Jaan; van der Veeken, Lennart; Attilakos, George; Eastwood, Mary Patrice; David, Anna Louise; Deprest, Jan
Abstract: Congenital diaphragmatic hernia is surgically correctable, yet the poor lung development determines mortality and morbidity. In isolated cases the outcome may be predicted prenatally by medical imaging. Cases with a poor prognosis could be treated before birth. However, prenatal modulation of lung development remains experimental. Fetoscopic endoluminal tracheal occlusion triggers lung growth and is currently being evaluated in a global clinical trial. Prenatal transplacental sildenafil administration may in due course be a therapeutic approach, reducing the occurrence of persistent pulmonary hypertension, either alone or in combination with fetal surgery.